Solubility Enhancement and Delivery Systems of Curcumin a Herbal Medicine: A Review - Hani, Umme; Shivakumar, H.G. (Current Drug Delivery, 2014)
Curcumin diferuloylmethane is a main yellow bioactive component of turmeric, possess wide spectrum of biological actions. It was found to have anti-inflammatory, antioxidant, anticarcinogenic, antimutagenic, anticoagulant, antifertility, antidiabetic, antibacterial, antifungal, antiprotozoal, antiviral, antifibrotic, antivenom, antiulcer, hypotensive and hypocholesteremic activities. However, the benefits are curtailed by its extremely poor aqueous solubility, which subsequently limits the bioavailability and therapeutic effects of curcumin. Nanotechnology is the available approach in solving these issues. Therapeutic efficacy of curcumin can be utilized effectively by doing improvement in formulation properties or delivery systems. Numerous attempts have been made to design a delivery system of curcumin. Currently, nanosuspensions, micelles, nanoparticles, nano-emulsions, etc. are used to improve the in vitro dissolution velocity and in vivo efficiency of curcumin. This review focuses on the methods to increase solubility of curcumin and various nanotechnologies based delivery systems and other delivery systems of curcumin.
Keywords: solubility enhancement